2004
DOI: 10.1007/bf02707275
|View full text |Cite
|
Sign up to set email alerts
|

Infrared reflection absorption study of water interaction with H-terminated Si(100) surfaces

Abstract: Water adsorption on clean and hydrogenated Si(100) surfaces was studied under ultra high vacuum conditions using surface infrared spectroscopy. The study shows that H-Si-Si-OH and SiH 2 species are formed on Si(100)-(2 × 1) and Si(100)-(2 × 1)-H surfaces, respectively. The reactivity behaviour of Si(100)-(3 × 1)-H and Si(100)-(1 × 1)-H is similar, both stabilizing oxygen inserted silicon dihydrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The spectra collected at 74° incidence also exhibited peaks at 3620, 1294, 920, and 836 cm –1 . The signal at 3620 cm –1 indicated O–H stretching, while the signals at 920 and 836 cm –1 were characteristic of O–H bending and Si–O stretching, respectively. The signal at 1294 cm –1 was tentatively assigned to O–H stretching coupled with O–H bending, following the analogous signal observed at 1080 cm –1 for methoxylated Si(111) surfaces that arises from O–C stretching coupled with CH 3 rocking . The observed signals suggested that a significant portion of the surface was hydroxylated and contained Si–OH functionality.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The spectra collected at 74° incidence also exhibited peaks at 3620, 1294, 920, and 836 cm –1 . The signal at 3620 cm –1 indicated O–H stretching, while the signals at 920 and 836 cm –1 were characteristic of O–H bending and Si–O stretching, respectively. The signal at 1294 cm –1 was tentatively assigned to O–H stretching coupled with O–H bending, following the analogous signal observed at 1080 cm –1 for methoxylated Si(111) surfaces that arises from O–C stretching coupled with CH 3 rocking . The observed signals suggested that a significant portion of the surface was hydroxylated and contained Si–OH functionality.…”
Section: Resultsmentioning
confidence: 90%
“…TIR spectra (Figure ) exhibited peaks ascribable to Si–OH vibrational modes, with the Si–O bond oriented perpendicular to the surface. , The O–H stretching signal exhibited a reduced intensity at 30° incidence, suggesting that the transition was polarized perpendicular to the surface. However, the proposed geometry of a surface-bound Si–O–H group would be expected to have a significant component of the O–H stretch oriented parallel to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a large number of studies have been reported on individual water molecules adsorbed on well-defined silicon surfaces using cutting-edge analytical methods in surface science [8][9][10]. To our knowledge, however, the WCA measurement has not been applied to the well-defined silicon surfaces prepared by ultrahigh vacuum (UHV) techniques, possibly because of incompatibility between water droplets and UHV environments.…”
Section: Introductionmentioning
confidence: 98%